„Ja jestem Bogiem, a nie człowiekiem!” (Oz 11,9). Prorocka wizja doskonałej miłości Boga „ojca mającego serce matki” - Kot, Piotr (Verbum Vitae, 2013)
Since the 1960s, in the circles of the so called feminist theology, there has been a strong call for a departure from the androcentric image of God in the exegesis of biblical texts. It initialized a differentiation, very radical at times, into fatherly and motherly features of God. This dualistic approach is evident especially in the aspect of God’s love to the human. However, a thorough analysis of the prophetic texts by Hosea and Isaiah, in which we find the metaphor of God’s motherly love, also leads to a significant observation that these authors never fragment God’s qualities, but present them as complementary: God loves the human with a love that is fatherly and motherly at the same time. God is a perfect being. The Scripture is a testimony of God who is Fullness (see: Col 1:19; 2:9; Eph 1:23; 3:19) and as such he gives himself to the human. Exposed to the effect of the loving God, the human receives a love that in the material world is associated with either male or female features, but which – in itself – is simply divine.